KAJIAN LITERATUR TENTANG PERAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTITIFAN BELAJAR SISWA SEKOLAH DASAR - Aina Dheabadra; Fatimatuz Zhahra; Hayatun Syifa; Septiana Devi Puspitasari; Wahdah Refia Rafianti; Ahmad Suriansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the role of Wordwall media in developing the learning activities of elementary school students. This study is motivated by the need for digital learning media that is attractive and appropriate to the characteristics of elementary school students who are active, enjoy playing, and responsive to interactive visual displays. The method used is a literature study by analyzing 12 relevant journals regarding the use of word walls in various subjects. The results of the analysis prove that word walls have a positive impact on student learning activities, which is seen from the increase in cognitive, affective, and psychomotor aspects as well as various indicators of activity such as asking questions, discussing, answering questions, and playing an active role during teaching and learning activities. In addition, word walls can increase interest and motivation in learning due to their interactive and fun game features. Overall, word walls are recommended as an effective digital learning medium to increase the learning activities of elementary school students.